A belief in trend reversal requires access to cognitive resources. Issue 2 (17th February 2017) - Tyszka, Tadeusz; Markiewicz, Łukasz; Kubińska, Elżbieta; Gawryluk, Katarzyna; Zielonka, Piotr
ABSTRACT: There are two research traditions studying people's reactions to random binary events: one concerns serial choice reaction times, the other concerns predictions of events in a series. The present studies focused on comparing expectations between these two approaches. We formed and tested a general hypothesis that, regardless of the type of task, when an individual faces a sequence of events they initially expect trend continuation. Only when people assume that a sequence is random might they override the default and expect trend reversal instead. In a series of experiments we found that limitation of access to cognitive resources enhances expectations of trend continuation. Our interpretation of this finding is that an expectation of trend continuation is the default for the human cognitive system and that a belief in trend reversal requires access to cognitive resources to overcome the tendency to expect trend continuation.